Socioepidemiological study and impact of reported leishmaniasis cases in Teresina, Piauí, Brazil (2014-2022) (Research, Society and Development, 2024)
Objective: To analyze the temporal, geographical, and socioeconomic factors that influence the incidence of leishmaniasis in Teresina between 2014 and 2022. Methodology: This study is based on an evaluation of secondary data obtained from the Information System for Notifiable Diseases (SINAN) through the TABNET website. The variables assessed were categorized into geographic, temporal, clinical, demographic, socioeconomic, and environmental categories. Results: A total of 1,246 cases of VLH and 300 cases of ATL were reported in Teresina over the historical series. The percentage of Teresina residents affected by VLH reached a maximum of 38.2%. ATL showed a higher percentage of residents affected, with a maximum of 67.1%. The profile of VLH patients was predominantly male (70.39%), mixed race (88.12%), aged between 20-39 years (27.37%), and had completed elementary education (14.37%). For ATL, the affected profile was mainly male (67%), mixed race (62%), aged between 40-59 years (34.33%), and had only completed elementary education (22%). Environmental data showed that most of Teresina's population has access to water supply and garbage collection services. However, deficient sanitation infrastructure affected 41.06% of the total population. Conclusion: The importance of strengthening surveillance and control strategies is highlighted, along with integrating health information systems for a more effective response.